Graphene and Carbon Nanotubes for Electronics Nanopackaging - Gabriele Boschetto (IEEE, 2021)
In recent years, the aggressive downscaling of electronic components has led to highly dense and power-hungry devices. With Moore’s law expected to soon reach its physical limit, there is a pressing need to significantly improve the efficiency and performance not only of nanodevices, but also of the embedding environment in which such nanodevices are integrated. In this context, key for improving the performance and for reducing both system cost and size is electronics packaging. However, electronics packaging at the nanoscale (i.e., nanopackaging) is currently facing several technological challenges, as in such scale conventional materials present intrinsic physical limitations. To address this, it becomes necessary to replace these latter with novel alternatives, such as low-dimensional carbon-based nanomaterials. Carbon nanotubes (CNTs) and graphene (materials with 1D and 2D dimensionality, respectively) have the potential to be successfully integrated into traditional silicon-based electronics as well as with beyond-silicon electronics, and their unique electrical, thermal, mechanical, and optical properties could be key enablers for significant performance improvements. In this short review we describe why these nanomaterials are very promising for electronics nanopackaging, and we outline the key application areas, mainly interconnects, thermal management, and flexible devices.